2016
DOI: 10.18632/oncotarget.9717
|View full text |Cite|
|
Sign up to set email alerts
|

Sirt3-mediated mitophagy protects tumor cells against apoptosis under hypoxia

Abstract: Sirt3, a mitochondrial deacetylase, participates in the regulation of multiple cellular processes through its effect on protein acetylation. The objective of this study was to explore the role of Sirt3 in the mitochondrial autophagy (mitophagy), a process of the specific autophagic elimination of damaged mitochondria. We found that silencing of Sirt3 expression in human glioma cells by RNA interference blunted the hypoxia-induced the localization of LC3 on the mitochondria, and the degradation of mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…VDAC1 can promote hexokinase II binding to mitochondria, which contributes to cancer cell metabolism, and inhibits damage to the mitochondria [40]. In addition, recent studies report that VDAC1 induces mitophagy via recruiting parkin to defective mitochondria to promote their degradation [34,41,42]. Sirt3 expression is increased by ToxH treatment, and the inhibition of Sirt3 with siSirt3 significantly suppressed the induction of mitophagy triggered by ToxH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VDAC1 can promote hexokinase II binding to mitochondria, which contributes to cancer cell metabolism, and inhibits damage to the mitochondria [40]. In addition, recent studies report that VDAC1 induces mitophagy via recruiting parkin to defective mitochondria to promote their degradation [34,41,42]. Sirt3 expression is increased by ToxH treatment, and the inhibition of Sirt3 with siSirt3 significantly suppressed the induction of mitophagy triggered by ToxH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked parkin, Sirt3, VDAC1, and hexokinase II with drug-resistant mitophagy [34]. Sirt3 is a sirtuin and nicotinamide adenine dinucleotide protein deacetylase that mainly localizes to the mitochondria and controls acetylation of mitochondrial proteins [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Qiao et al revealed that Sirt3 activates mitophagy in hypoxic tumor cells. 13 Therefore, the regulation of mitophagy in tumor tissue is a candidate for clinical treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%